Internal Migration, Urbanization and Poverty in Asia: Dynamics and Interrelationships - Jayanthakumaran, Kankesu; Verma, Reetu; Wan, Guanghua; Wilson, Edgar (Springer Nature Singapore : Imprint: Springer, 2019)
This book is Open Access under a CC BY license. Asia's recent demographic transitions and rural-urban structural transformations are extraordinary and involve complexities that require in-depth study. The chapters within this volume examine those complexities using a range of traditional and nontraditional measures-such as multidimensional poverty, gaps, and polarization-to arrive at the conclusion that poverty is now an urban issue. This volume offers an essential resource for economic policy makers and students of development economics to understand the interrelationships between internal migration, urbanization, and poverty in Asia, paving the way for the improved management of internal migration, and disadvantaged and vulnerable populations. Kankesu Jayanthakumaran is a Senior Lecturer at the University of Wollongong, Australia. His research has chiefly concentrated on 'trade facilitation and performance', an area in which he has published 30 peer-reviewed journal articles and five book chapters, edited two books, and authored one: Industrialization and Challenges in Asia, published in 2016. Reetu Verma is a Senior Lecturer and one of the Heads of Students in the Faculty of Business at the University of Wollongong, Australia. Reetu's main areas of expertise are in the fields of economic growth and development, student engagement and support, statistics/quantitative techniques, and applied econometrics. Guanghua Wan is Director of the Institute of World Economy, Fudan University, People's Republic of China. Previously he worked for the Asian Development Bank, the United Nations and the University of Sydney. With a background in development economics and econometrics, Dr. Wan is a multi-award-winning scholar on the Chinese economy and an expert on Asia, with an outstanding publication record of more than 100 professional articles and a dozen books. Ed Wilson is an Associate Professor at the University of Wollongong, Australia. A former president of the Economic Society of Australia, New South Wales, his research interests are in macroeconomic modelling, empirically gauging the determinants of economic growth and productivity, and the consequences of policies to reduce poverty and child labor in Asia.